Mapeamento geotécnico preliminar em escala de semi-detalhe (1:25.000) da área de expansão urbana de Uberlândia-MG - Andrade, Ricardo Fernandes de (2005)
This research presents the preliminary Engineering Geological Mapping of an contour area of the urban portion of the city of Uberlândia western of the state of Minas Gerais in a scale of semi-detail (1:25.000), covering approximated an area of 303 Km². The development of this work had as a general objective to provide subsidies to the planning of the use and occupation of the urban environment having the characterization and delimitation of geotechnical unities as a starting point. The development of the mapping followed the methodology proposed by the Escola de Engenharia de São Carlos - USP, proposed by Zuquette (1987). As a final result, three cartographic documents were elaborated: a Document Map, a Declivity Chart and a Map of Unconsolidated Materials. The Map of Unconsolidated Materials was generated by the analysis of the following attributes related with the unconsolidated covering: type and nature, texture, thickness and analysis of the results of Standard Penetration Tests for definition of the thickness of the materials, not only in the regions with higher index of urbanization but also on those with lower one, and field rehearsals and laboratory. They were identified 9 geotechnical unities of unconsolidated materials. All the materials of the studied area were characterized as colapsíveis. The soils of six of these units, they were characterized as lateríticos of the types LA and LA' (according to the classification MCT) and, when appraised as for their mechanical and hydraulic properties after the compacting, they presented high Bearing capacity, low permeability, low expansibility and low to medium contraction. They are the most indicated for pavement base, sub grade reinforcement, compacted embankment and primary covering. Key Words: engineering geological mapping, urban planning; unconsolidated materials; environment.